Do Patients With Inflammatory Bowel Disease Benefit from an Enhanced Recovery Pathway?. Issue 3 (2nd August 2019) - Liska, David; Bora Cengiz, Turgut; Novello, Matteo; Aiello, Alexandra; Stocchi, Luca; Hull, Tracy L; Steele, Scott R; Delaney, Conor P; Holubar, Stefan D
Abstract: Background: Enhanced recovery pathways (ERPs) have been shown to reduce length of stay (LOS), complications, and costs after colorectal surgery; yet, little data exists regarding patients with inflammatory bowel disease (IBD). We hypothesized that implementation of ERP for IBD patients is associated with shorter LOS and improved economic outcomes. Methods: An IRB-approved prospective clinical database was used to identify consecutive patients from 2015 to 2017. Patients were grouped as "pre-ERP" and "post-ERP" based on the date of implementation of a comprehensive ERP. Ileostomy closures, redo pouch operations, and outpatient operations were excluded. The relationship between ERP, LOS, and secondary outcomes was assessed using univariate and multivariate analysis. Results: Overall, a total of 671 patients were included: 345 (51.4%) with Crohn's disease (CD) and 326 (48.6%) with ulcerative colitis (UC). Of these, 425 were pre-ERP (63.4%), and 246 were post-ERP (36.6%). The groups did not differ in terms of age, gender, American Society of Anesthesiologist (ASA) scores, comorbidities, estimated blood loss, or ostomy construction. The post-ERP group had a significantly higher mean body mass index (BMI), more patients with CD, longer operative time, and more minimally invasive surgery (MIS; all P < 0.05). The post-ERP group had a significantly shorter LOS (6 vs 4.5 days, median), whereas mean hospital costs decreased by 15.7%. There was no difference in readmissions or complications. On multivariate analysis, MIS and ERP use were both associated with a shorter LOS. Conclusion: Inflammatory bowel disease patients benefit from the use of ERP, demonstrating decreased LOS and costs without an increase in complications and readmissions. Enhanced recovery pathways should be routinely implemented in this often challenging patient population. Abstract : Enhanced recovery pathways (ERPs) improve outcomes following colorectal surgery. Little data exists regarding patients who undergo surgery for inflammatory bowel disease. In this paper we show that ERP implementation in this high risk group results in decreased length of stay and costs, without an increase in complications or readmissions.